Evaluating the Role of Microbicides in Antibiotic Resistance Development in Clinical Pathogens (Sebha University Conference Proceedings, 2024)
A group of microbicides such as disinfectants and antiseptics are commonly used in healthcare settings to control cross contamination, outbreak of diseases, and hospital-acquired infections.  Yet, concerns have been raised in recent years regarding co-selection for antibiotic resistance among pathogenic bacteria genre after repeated exposure to microbicide.  The aim of this study was therefore to evaluate the effect repeated exposure of povidone-iodine (PVP-I) and surfanios premium at sub-inhibitory concentrations on antibiotic resistance in K. pneumoniae.    Methods & Material: Twenty clinical pathogens of K. pneumoniae strains were obtained from various clinical samples of patients admitted at  Aljala Trauma hospital,  Benghazi, Libya were identified by standard  microbiological and chemical methods at  microbiology laboratory of hospital.  MICs of biocides were determined by the broth dilution method; antibiotics susceptibility was performed were tested using Kirby and Bauer disk diffusion method.  MICs and antibiotic susceptibilities were determined before and after repeated exposure to to sub-inhibitory concentrations of biocides (sub-MICs) to test for changes in biocide tolerance and Co-selection resistance to antibiotics.   Result: Our results show that 5 out of 20 K. pneumoniae isolates (25%) exhibited an acquired tolerance to PVP-I.  In this study was observed subtle of susceptibility changes to ceftriaxone, cefotaxime, ciprofloxacin, levofloxacin, and amikacin in  K. pneumoniae isolates after exposure to sub-MIC concentrations of biocides.   Conclusions: Use low suboptimal concentrations biocides may increase antibiotic resistance in clinically relevant bacteria such as K. pneumoniae.   Therefore, further studies are needed to evaluate whether these associations are causal.